Adulteration of anthocyanin- and betalain-based coloring foodstuffs with the textile dye 'Reactive Red 195' and its detection by spectrophotometric, chromatic and HPLC-PDA-MS/MS analyses. (December 2016) - Müller-Maatsch, Judith; Schweiggert, Ralf M.; Carle, Reinhold
Abstract: A wide range of natural food colorants and coloring foodstuffs is available for the food industry to meet current costumer trends. Most natural pigments are more sensitive towards heat, light, and pH changes compared to their synthetic counterparts. Additionally, high dosages are often required to attain desired color hues and intensities. In this research article, we report on the broad and worldwide incidence of a fraudulent practice to overcome these disadvantages by adding a non-approved azo-dye preparation originating from the textile dye Reactive Red 195 to natural pigment extracts. Since the respective products and their derivatives have been widely distributed, we present a rapid method allowing the differentiation of the fraudulent azo-dye from Hibiscus sabdariffa (roselle) flower and Beta vulgaris (red beet) root extracts, the two coloring foodstuffs that are most frequently adulterated. Furthermore, detailed HPLC-PDA-MS/MS data is presented for the unambiguous identification of Reactive Red 195 and its derivatives. Highlights: The fraudulent addition of a textile dye to coloring foodstuffs is reported. Roselle and red beet were found to be adulterated with Reactive Red 195 (RR 195). Characterization of RR 195 by physico-chemical methods and HPLC-PDA-MS/MS. Methods for the differentiation of anthocyanins, betalains, and RR 195. Actual examples of fraudulent adulterations from food companies worldwide.